Smoking Initiation in Germany: The Role of Intergenerational Transmission - Lenz, Silja; Schmidt, Christoph; Tauchmann, Harald (Health Economics, 2010)
This paper analyzes the decision to start smoking using data from the German Socio-Economic Panel (GSOEP). Our focus is on the role that parental smoking behavior plays for children's smoking initiation. The data used are a combination of retrospective information on the age individuals started smoking and, by tracing back these individuals within the panel structure up to that point, information on characteristics at the age of smoking initiation. In contrast to the previous literature it is possible to control for the environment at the time of smoking onset that might have influenced the decision to start. Our preferred specification of a discrete time hazard model indicates that parental smoking significantly increases the offspring's hazard to start smoking. While this effect is most prominent for currently smoking parents, it is also found for parents who have given up smoking already. However, an ambiguous effect of the timing of parental smoking cessation is found, arguing against role-model effects being a key determinant for smoking initiation. Copyright © 2009 John Wiley & Sons, Ltd.
WiSo-Import:2015-03-26:4665
Keywords: Discrete time hazard model; GSOEP; Intergenerational transmission; Youths